Are preferential agreements beneficial to EU trade? New evidence from the EU-South Korea treaty - Beniamino Quintieri; Giovanni Stamato (European Central Bank (ECB), 2023)
This paper empirically investigates the effect of the EU-South Korea free trade agreement (FTA) on manufacturing trade flows. By applying a state-of-the-art structural gravity model with intranational (i.e., domestic) trade and using disaggregated data, we quantify both the trade impact and the observed heterogeneity in the FTA estimates. In line with literature, we find that the FTA exerted asymmetric effects in bilateral exports across directions of trade. Compared to previous studies, our findings suggest a different explanation for the poor performances of Korean exports to the EU in the post-FTA period, namely offshoring patterns in electronics and a broad-based decline in the shipbuilding industry. When we drop these two export categories from the analysis, we show that the FTA exerted a large effect on trade in both directions, increasing bilateral exports by about 30 percent. We then investigate heterogeneity in pair-industry-specific estimates of the FTA. The main source of variation is represented by asymmetries in ex ante trade barriers across sectors, with a prominent role for non-tariff instruments. Stronger pre-FTA regulatory intensity is associated to a high liberalization potential, favouring larger FTA estimates.
Keywords: F10; F13; F14; 330; EU-South Korea FTA; structural gravity models; heterogeneous trade effects